2014
DOI: 10.1007/s13191-014-0390-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distribution Around Single Short Dental Implants: A Finite Element Study

Abstract: Bone height restrictions are more common in the posterior regions of the mandible, because of either bone resorption resulting from tooth loss or even anatomic limitations, such as the position of the inferior alveolar nerve. In situations where adequate bone height is not available in the posterior mandible region, smaller lengths of implants may have to be used but it has been reported that the use of long implants (length ≥10 mm) is a positive factor in osseointegration and authors have reported failures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Assessing the effect of the axial force, was detected the distribution of uniform stress in peri-implant bone without concentrations in a specific surface area of the implant [24,25,27,28,36]. These FEA findings are close to results of in vivo studies.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Assessing the effect of the axial force, was detected the distribution of uniform stress in peri-implant bone without concentrations in a specific surface area of the implant [24,25,27,28,36]. These FEA findings are close to results of in vivo studies.…”
Section: Discussionsupporting
confidence: 68%
“…Also, implant design characteristics were described as factors causing the stress. The alteration of stress was related with implant length [21,24,29], width [21,25,26,28-31], macro-relief as thread [28,32], and micro-relief as porosity [27]. Some of the articles emphasized that stress changes were caused by platform switching connection [20-22,33].…”
Section: Resultsmentioning
confidence: 99%
“…Heat-cured resin was used for fabricating the models as its modulus of elasticity is closer to natural cancellous bone. [ 9 10 11 ] The models were designed with a slit in the center of the base to simulate the L-shape and the flexion of the mandible. Implant analogs of dimension 3.75 mm × 11.5 mm were placed in the following tooth positions; 36, 33, 43, 46.…”
Section: Discussionmentioning
confidence: 99%
“…Many current in vivo and in vitro studies have tried to assess the impact of implant dimensions on the stress transmitted to the peri-implant tissue but have yet to reach a clear conclusion on this complex matter. [ 4 5 6 7 8 ] Some studies have reported that a larger implant may lead to smaller stress values in the peri-implant bone. [ 5 6 7 ] However, other studies show that smaller implants used in resorbed mandibles have a comparable long-term survival rate and stress values to larger implants.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 5 6 7 8 ] Some studies have reported that a larger implant may lead to smaller stress values in the peri-implant bone. [ 5 6 7 ] However, other studies show that smaller implants used in resorbed mandibles have a comparable long-term survival rate and stress values to larger implants. [ 4 5 6 ] Furthermore, there is a lack of studies on the importance of bone geometry and its influence on the implant induced stress at the crestal bone level, since implant dimensions, stress, and bone geometry are all inter-related and should not be studied separately.…”
Section: Introductionmentioning
confidence: 99%